2009
DOI: 10.1002/prot.22545
|View full text |Cite
|
Sign up to set email alerts
|

Conformational selection and collagenolysis in Type III collagen

Abstract: Matrix metalloproteases (MMPs) cleave native collagen at a single site despite the fact that collagen contains more than one scissile bond that can, in principle, be cleaved. For peptide bond hydrolysis to occur at one specific site, MMPs must (1) localize to a region near the unique scissile bond, (2) bind residues at the catalytic site that form the scissile bond, and (3) hydrolyze the corresponding peptide bond. Prior studies suggest that for some types of collagen, binding of noncatalytic MMP domains to am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 77 publications
(107 reference statements)
1
21
0
Order By: Relevance
“…Similarly, type I collagen heterotrimer has a conserved Pro at the P 3 subsite suggesting that one chain may have more flexibility at the Ile/Leu site than the other two chains. These data support the studies that have shown that only a single chain of collagen can be incorporated into the active site cleft of MMPs and that type I collagen is cleaved by MMPs one chain after the other (32,34).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, type I collagen heterotrimer has a conserved Pro at the P 3 subsite suggesting that one chain may have more flexibility at the Ile/Leu site than the other two chains. These data support the studies that have shown that only a single chain of collagen can be incorporated into the active site cleft of MMPs and that type I collagen is cleaved by MMPs one chain after the other (32,34).…”
Section: Discussionsupporting
confidence: 90%
“…NMR studies of an unlabeled heteromeric triple helical peptide containing the cleavage site of type I collagen indicate that the cleavage site region has less ordered structure than the ends with GPO repeating triplets (62). Recent simulations of type III collagen have shown that the whole cleavage site is relatively exposed to solvent, and it samples structures that are more complementary to the MMP active site (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MD simulations were used by Salsas-Escat and Stultz (2010) to generate ensembles of type III collagen that describe its conformational heterogeneity. They observed that collagen could adopt in the free state the configuration that it adopts in the active site of proteolytic enzyme CMMP8 that cleaves disordered peptides.…”
Section: Biomolecular Recognition From Ensemblesmentioning
confidence: 99%
“…Several G-[I/L]-[A/L] triplets are present in native collagen, indicating that, in principle, other scissile bonds may exist. However, with the exception of MMP-13, most MMPs primarily cleave the collagen helix at a single location, reflecting the importance of the unique sequence which surrounds the cleavage site (13, 14). …”
Section: Introductionmentioning
confidence: 99%